Instruments of Communicative Skill According to 4C's In Trigonometric Ratio - Fitri Umardiyah; Ninik Maslukhah (APPLICATION: Applied science in Learning Research, 2022)
The purpose of this research is to develop mathematics learning instruments in the form of communicative skills-based modules that conform to 4C's criteria on trigonometric ratio. This research uses Research and Development methods adapted in the development of the ADDIE model. The subjects of this study were class X learners at Madinatul ‘Ulum Jombang High School for the academic year 2020/2021. As for data collection techniques are interviews and questionnaires. Researchers designed a learning instrument in the form of communicative-based modules. The results of this study showed that (1) Assessment of the validity of learning instruments in the form of communicative-based modules by two material experts received a percentage of 94% and 75.5% with a very valid and quite valid category. (2) Assessment of the practicality of learning instruments in the form of communicative-based modules by learners gets a percentage of 82.07% with a very practical category. Based on the results of the above research, researchers concluded that learning instruments in the form of communicative-based modules are declared valid and practical based on the assessment of experts and learners, so it is worth using in mathematical learning.